2022
DOI: 10.3389/fmicb.2022.858508
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome Succession in Chinese Mitten Crab Eriocheir sinensis During Seawater–Freshwater Migration

Abstract: Biological migration is usually associated with disturbances and environmental changes that are key drivers in determining the diversity, community compositions, and function of gut microbiome. However, little is known about how gut microbiome is affected by disturbance such as salinity changes during migration from seawater to freshwater. Here, we tracked the gut microbiome succession of Chinese mitten crabs (Eriocheir sinensis) during their migrations from seawater to freshwater and afterward using 16S rDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…Our results showed that the alpha diversity of microbes showed hump patterns in guts during developments ( Figure 4 ). This finding is consistent with observations in Eriocheir sinensis and other animals such as Atlantic salmon [ 19 , 63 ]. During the process of the seawater–freshwater transition, the species richness of the gut microbiome of Eriocheir sinensis shows a hump-shaped trend, while the abundance of the gut microbiome of Atlantic salmon shows a hump-shaped pattern after transferring from the same hatchery to circulating aquariums and open lakes.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that the alpha diversity of microbes showed hump patterns in guts during developments ( Figure 4 ). This finding is consistent with observations in Eriocheir sinensis and other animals such as Atlantic salmon [ 19 , 63 ]. During the process of the seawater–freshwater transition, the species richness of the gut microbiome of Eriocheir sinensis shows a hump-shaped trend, while the abundance of the gut microbiome of Atlantic salmon shows a hump-shaped pattern after transferring from the same hatchery to circulating aquariums and open lakes.…”
Section: Discussionsupporting
confidence: 93%
“…For megalopa samples, surfaces were rinsed using sterile water and hindgut contents were collected by dissecting needles. According to the different developmental stages of Eriocheir sinensis after the completion of desalination [ 19 ], we collected intestinal samples a total of three times, the first time in Dongtai, Rudong and Sheyang to collect Eriocheir sinensis megalopa in desalination ponds regarded as the initial stage of the completion of desalination (Day 1), and the second and third time were both in the Hohai University sterile plastic baskets. The second and third time were collected in sterile plastic baskets at Hohai University as the environmental adaptation stage (Day 5) and the developmental completion stage (Day 9), in which the collected samples were in the Eriocheir sinensis megalopa stage on Day 1 and Day 5, and in the first juvenile stage on Day 9, so a total of 54 Chinese mitten crab intestinal samples were collected (that is, 3 time points × 3 sites × 6 replicates).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be influenced by several factors, including genetic background, sex, developmental stage, habitat environment, feed type, health conditions, and external stimuli ( Piazzon et al, 2020 ). While nongenetic factors have been extensively studied for their impact on the changes in the intestinal microorganisms of E. sinensis ( Chen et al, 2021a , b ; Guan et al, 2021 ; Guo et al, 2021 ; Jiang et al, 2022 ; Shao et al, 2022 ), little research has been conducted on the effects of host genetic background on the composition of the intestinal microflora in this economically significant species. This study investigated the gut microbiome communities and metabolic profiles in juveniles of two E. sinensis crab varieties with different shell colors.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota composition is shaped by the host’s genetic background, developmental stage, health status, and environment ( Ussar et al, 2016 ; Cahana and Iraqi, 2020 ; Li et al, 2021 ; Qin et al, 2022 ). Researchers have performed many studies comparing the gut microbiota of E. sinensis among different environments, diets, and ages and that of healthy and diseased individuals ( Ding et al, 2017 ; Wang et al, 2019 ; Chen et al, 2021b ; Shao et al, 2022 ; Xu et al, 2022 ). However, reports related to host genetic backgrounds are scarce.…”
Section: Introductionmentioning
confidence: 99%